G441 History of paediatric nephrology in europe – 50 years of hope. (12th March 2018) - Tse, Y; Maxwell, H; Watson, AR; Levtchenko, E; Christian, M
Abstract : 2017 marked the 50th anniversary of the European Society for Paediatric Nephrology (ESPN) foundation meeting in Glasgow. It was also the centenary of the first ever kidney biopsy in a child or adult also in Glasgow. Since then tremendous advances in medical, nursing and psycho-social care have been made. As part of the anniversary we held and recorded on film a history symposium delivered by early pioneers. Topics included the start of dialysis and transplantation in children, use of renal biopsy to in nephrotic syndrome management, collaborative work of the ESPN and development of the multi-disciplinary team. Creating this opportunity for retired experts to reflect on 50 years of progress gives a unique wide-angled perspective. These journeys of discoveries challenges current thinking and can act like a calibrating device to ensure good past ideas are not lost. We also created an oral history video repository (www.youtube.com/c/ESPNhistory) where 35 early pioneers recorded their stories for (P)ity. Their voices recount vividly the desperation families and children suffered when treatment was ineffective and transplant or dialysis unfathomable – followed by the era of rapid innovation. We learn from the pioneers their own personal stories of self-sacrifice, heroism and dogged persistence. Of interest to our current generation is the historical and technological context: the Iron Curtain curtailing travel, no internet, emails or Medline. These pioneers matured research from personal case series to the international collaborations we have today. Storing oral history is important as most of this rich history was never written up, remembered only in anecdotes. With today's inexpensive technology it is simple and we achieved breath by collaborating internationally. We owe it to future generations to collate a living oral history of medicine of this remarkable bygone age from those who were there. The use of cheap smartphone filming and a customised repository channel on internet video social media opens up new ways to connect history of medicine to future generations.